Functional Expression of TRPV1 Ion Channel in the Canine Peripheral Blood Mononuclear Cells - Bujak, Joanna K. (Int J Mol Sci, 2021)
TRPV1, known as a capsaicin receptor, is the best-described transient receptor potential (TRP) ion channel. Recently, it was shown to be expressed by non-excitable cells such as lymphocytes. However, the data regarding the functional expression of the TRPV1 channel in the immune cells are often contradictory. In the present study, we performed a phylogenetical analysis of the canine TRP ion channels, we assessed the expression of TRPV1 in the canine peripheral blood mononuclear cells (PBMC) by qPCR and Western blot, and we determined the functionality of TRPV1 by whole-cell patch-clamp recordings and calcium assay. We found high expression of TRPV2, -M2, and -M7 in the canine PBMCs, while expression of TRPV1, -V4 and, -M5 was relatively low. We confirmed that TRPV1 is expressed on the protein level in the PBMC and it localizes in the plasma membrane. The whole-cell patch-clamp recording revealed that capsaicin application caused a significant increase in the current density. Similarly, the results from the calcium assay show a dose-dependent increase in intracellular calcium level in the presence of capsaicin that was partially abolished by capsazepine. Our study confirms the expression of TRPV1 ion channel on both mRNA and protein levels in the canine PBMC and indicates that the ion channel is functional.